Aripiprazole once-monthly long-acting injectable for the treatment of schizophrenia. (11th February 2016) - Potkin, Steven G; Preda, Adrian
ABSTRACT: Introduction : Patient non-adherence increases the risk for relapse and the long-term care of schizophrenia. Long-acting injectable (LAI) antipsychotics can decrease this risk by ensuring adherence. An extended formulation, aripiprazole 400 mg once-monthly (AOM 400) LAI (AOM LAI), received regulatory approval in the year 2013 for the treatment of schizophrenia. AOM LAI is the first dopamine D2 partial agonist available in a long-acting formulation for the treatment of schizophrenia. Areas covered : This review covers data on the efficacy and tolerability/safety of AOM LAI. AOM LAI is a lyophilized powder of aripiprazole, with an elimination half-life of 29.9 – 46.5 days, allowing for a 4-week injection interval. Antipsychotic efficacy was documented in a 12-week double-blind trial (n = 340) and in two maintenance-of-effect trials: a 38-week trial (n = 662) and a 52-week trial (n = 403). The side effect profile is similar to that of oral aripiprazole. Adverse events (≥5% and at least twice that for placebo) were typically mild or moderate and did not lead to discontinuation: increased weight, akathisia, injection site pain and sedation. The 400 mg dose is tolerated by >90% of patients. Injection does not require additional training of health personnel or post-injection observation. Expert opinion : AOM LAI is an efficacious and well-tolerated antipsychotic treatment for schizophrenia.